Monitoring regional economic policy effectiveness of the Donetsk People’s Republic in anti-crisis management strategies agricultural complex implementation - O. L. Nekrasova; R. S. Blizkiy; M. G. Gorobets (Вестник университета, 2024)
The article studies theoretical and methodological aspects of monitoring of re gional economic policy, as well as a comparative analysis of key areas of regional policy with the Russian constituent entities. The unique factors and special conditions affecting the development of the Donetsk People’s Republic (hereinafter – DPR) regional economic policy have been outlined, the convergence processes at the meso- and macro-levels to the average indicators of Russian economic well-being noted. The realization concept of the anti-crisis management in the agricultural complex of the DPR strategy, considered from the position of interfering effective economic and managerial decision affecting positive results achievement in ensuring the stability of the DPR regional economic policy corresponding directions, has been proposed. The matrix of the crisis management methods application optimality has been developed, considering the criteria of segmenting application frequency and cost aggregation index.   The purpose of the study is to substantiate DPR’s effective regional policy monitoring in interfering its sustainable elaboration of the successful implementation of the anti-crisis management strategy causal dependence on the example of the agricultural complex.